Differences in antibiotic prescribing quality in Belgian out-of-hours primary care services. Issue 2 (4th March 2023) - De Man, Jeroen; Remmen, Roy; Philips, Hilde
ABSTRACT: Objectives: This study aims to compare trends in antibiotic prescribing behaviour for lower urinary tract infections among different out-of-hours primary care services. Methods: Cross-sectional study using routine prescription data extracted from electronic health records from six out-of-hours services. The study population included 5888 cases diagnosed with an uncomplicated lower urinary tract infection from 2016 to 2020. Prescriptions were assessed based on the national guidelines. Results: Considering the total study period, an antibiotic was prescribed in 98.9% of cases. Among these cases, 55.0% was prescribed a guideline recommended antibiotic, 21.0% was prescribed fosfomycin, 17.4% was prescribed a quinolone and 1.8% was prescribed more than one antibiotic. Guideline recommended prescribing improved substantially over time. However, there were significant differences among out-of-hours services in terms of proportion over the total study period (between 49.0% and 66.7%) as well as in terms of time-trend pattern. Conclusion: Substantial differences among out-of-hours services suggest a potential for further improvement in the quality of antibiotic prescribing. Monitoring prescribing behaviour per out-of-hours primary care service can guide focused interventions.